Pendidikan Islam Dalam Keluarga: Upaya Membentuk Kepribadian Anak - Saruji (MGMP SMP PAI Provinsi Riau, Indonesia, 2022)
Islamic education is an effort to prepare humans to know, understand, live, and believe in the teachings of the Islamic religion. Islamic education in the family should be given early, because the family is as the first and main living environment for the child and must be the first madrasa for the growth and development of his soul. The family has an important role in preparing the child for social life, the influence of parents, siblings, and other family members on the behavior of the child at school becomes very strong. From parents and social friends, the child acquires many fundamental directions to attend school and follow the educational process. This article explains that the importance of instilling Islamic education in the family begins with faith education, worship education and education in reading the Qur'an and moral education. Furthermore, what are the responsibilities and obligations that must be fulfilled by parents towards children and how to treat children in the family.